Systemic lupus erythematosus in Latin America: Outcomes and therapeutic challenges - Ugarte-Gil, Manuel F. (2023)
Systemic lupus erythematosus (SLE) affects more severely non-White populations, which is also the case in Latin America; this is the result of a combination of genetic and non-genetic factors. Among the non-genetic factors, a limited income and a low educational level impact negatively on the course and outcome of the disease; in addition, lack of access to healthcare services deprives patients from the opportunity of being managed by specialists, making the availability of the newest drugs practically impossible. Taking together, these factors reduce the probability of patients achieving good outcomes, like remission, less damage accrual, a better survival and a better health-related quality of life, among others. Several strategies have been proposed to reduce these disparities, including peer education, educational activities for patients and primary care physicians, improving healthcare networks and generating cost-effectiveness analyses.